KOMBINASI PEMBERIAN MAKANAN TAMBAHAN DENGAN EDUKASI KESEHATAN PADA ANAK SEKOLAH DI KOTA SIBOLGA - Chahyanto, Bibi Ahmad; Hasfika, Ivonna; Susilo, Yayuk (Universitas Mataram, 2024)
The nutritional status of school children needs to be maintained in good condition as it aids optimal growth and development, as well as improvement in learning achievements. Efforts that can be undertaken to preserve nutritional status include adopting a healthy dietary pattern and practicing clean and healthy lifestyle behaviors. Therefore, it is necessary to conduct community service activities that combine the provision of Supplementary Feeding Program (PMT) with health education for school-age children. This activity aims to analyze changes in weight, nutritional status, and health knowledge of school-age children before and after receiving a combination of supplementary feeding program and health education. The method employed involved combining the intervention of providing supplementary nutrition with community education targeted at fifth-grade school children at SDN 087695 and MIN 2 in the Sibolga City. The activities took place from July to September 2019 and were divided into three stages: preparation, implementation, and evaluation. The results of the activity indicate that both the school and students were enthusiastic in participating in community service. Students experienced an increase in weight, changes in nutritional status, and improvement in health knowledge. The students' weight increased significantly (p < 0.05) from an average of 29.50 ± 7.10 kg to 30.08 ± 7.06 kg. The percentage of good nutritional status increased from 67.57% to 72.97%, and the students' health knowledge scores also showed a significant improvement (p < 0.05) from an average of 3.70 ± 1.61 to 5.97 ± 1.38. The combination of supplementary feeding program with health education for school-aged children can enhance weight, nutritional status, and health knowledge.